Leader-member exchange and glass ceiling: the effects on career satisfaction and work engagement - Sinto Sunaryo; Reza Rahardian; Risgiyanti; Joko Suyono; Dian Ekowati (Cogent Business & Management, 2024)
The glass ceiling still exists in the workplace, where women face barriers to achieving a higher career path. One of the obstacles comes from the organizational environment in the form of gender stereotypes, which make it increasingly difficult for women to occupy managerial positions. In this case, leaders play an important role in building relationships with subordinates to overcome the glass ceiling issue. Not many studies analyze gender discrimination in the workplace from the perspective of social exchange between leaders and subordinates. This study aimed to analyze the effect of leader-member exchange on career satisfaction and work engagement through the glass ceiling. Data were collected from 469 female employees working in various companies in Indonesia. Convergent and discriminant validity were conducted to validate the measurement of variables, and the partial least squares were used to test the hypotheses. Leader-member exchange has been shown to have a negative effect on the glass ceiling. Similarly, the glass ceiling has a negative effect on career satisfaction and work engagement. In addition, the glass ceiling mediates the effect of leader-member exchange on career satisfaction and work engagement. Given these results, leaders need to build high quality relationships with employees to prevent a glass ceiling in the workplace.Discrimination against women continues to be an important issue in the workplace, with women facing barriers to leadership positions. Glass ceilings at work are often elusive. In this case, the leader's role becomes crucial. Leaders are responsible for building quality relationship with subordinates, and the quality of the relationship can determine career success, including overcoming career barriers for women. If women feel inhibited from reaching managerial positions, this will affect their career satisfaction and work engagement. This research provides an understanding of how the quality of the leader-subordinate relationship may impact the glass ceiling experienced by women and how it affects career satisfaction and work engagement. Therefore, it is necessary to maintain high quality relationships between leaders and subordinates in the workplace, as this can protect women from various forms of discrimination.
Keywords: 650; leader-member exchange; glass ceiling; career; satisfaction; work engagement